Do Derivatives Instruments Ownership Decrease Firm Value in Indonesia? - Firmansyah, Amrie; Purnama, Eko Bayu Dian (Universitas Muhammadiyah Surakarta, 2020)
This research aims to examine the association between derivatives instruments and firm value. This research is quantitative research with multiple linear regression models and panel data. The sample employed in this research is non-financial companies listed on the Indonesia Stock Exchange (IDX). The type of data used in this study is secondary data sourced from financial statements, stock price information, and annual reports from 2012 to 2017. The sample selection using a purposive sampling method with the number of samples amounted to 246 firm-year. The result of this study suggests that a derivatives instrument is not associated with firm value. Investors in Indonesia do not consider ownership of derivative instruments by companies whether those are harmful of not for the investment impact. Also, derivatives do not have an official market in Indonesia as well as investors also do not understand the purpose of derivative ownership by companies.